Analysis and Modeling Gross Domestic Product, Carbon Dioxide Emission, Population Growth, and Life Expectancy at Birth: Case Study in Qatar - Hasnawati, Sri; Usman, Mustofa; Faisol, Ahmad; Elfaki, Faiz A. M. (International Journal of Energy Economics and Policy, 2023)
Studies on Life Expectancy at Birth (LEB) and Population Growth (PG) with several economic variables for cases in Qatar have not been carried out much. The study of the relationship between Life expectancy at Birth(LEB), Carbon Dioxide(CO2)emission, Population growth(PG), and Gross Domestic Product(GDP)for the case of Qatar is interesting because it is a developed country based on oil and gas. The aims of this study is to build a dynamic model for vector time series that describes the relationship between the variables discussed. From the analysis results based on Criterion Information, Akaike’s Information Criterion Correction (AICC), and Cointegration Rank, the best model obtained is the Vector Error Correction Model with order 4 (VECM (4)) and with Cointegration Rank r=4. Based on this dynamic model, Granger-Causality analysis, Impulse Response Function (IRF), and Forecasting will be discussed.